Adverse events of raltegravir and dolutegravir. (24th August 2017) - Elzi, Luigia; Erb, Stefan; Furrer, Hansjakob; Cavassini, Matthias; Calmy, Alexandra; Vernazza, Pietro; Günthard, Huldrych; Bernasconi, Enos; Battegay, Manuel
Abstract : Objective: To compare the frequency and risk factors of toxicity-related treatment discontinuations between raltegravir and dolutegravir. Design: Prospective cohort study. Methods: All antiretroviral therapy (ART)-naïve and ART-experienced HIV-infected individuals from the Swiss HIV Cohort Study who initiated raltegravir or dolutegravir between 2006 and 2015 were investigated concerning treatment modification within the first year. Results: Of 4041 patients initiating ART containing raltegravir ( n = 2091) or dolutegravir ( n = 1950), 568 patients discontinued ART during the first year, corresponding to a rate of 15.5 [95% confidence interval (CI) 14.5–16.9] discontinuations per 100 patient-years. Only 10 patients on raltegravir (0.5%) and two patients on dolutegravir (0.1%) demonstrated virologic failure. The main reason for ART discontinuation was convenience expressed as patient's wish, physician's decision, or treatment simplification ( n = 302). Toxicity occurred in 4.3% of patients treated with raltegravir and 3.6% with dolutegravir, respectively. In multivariable analysis, the only independent risk factor for discontinuing ART because of toxicity was female sex (hazard ratio 1.98, 95% CI 1.45–2.71, P < 0.001). Neuropsychiatric complaints were the most commonly reported toxic adverse events and more frequent in the dolutegravir ( n = 33, 1.7%) compared with the raltegravir group ( n = 13, 0.6%). Risk of discontinuation for neurotoxicity was lower for raltegravir than for dolutegravir in multivariable analysis (hazard ratio 0.46, 95% CI 0.22–0.96, P = 0.037). Conclusion: In this, large cohort raltegravir and dolutegravir-containing regimen demonstrated a high virologic efficacy. Drug toxicity was infrequent and discontinuation because of neuropsychiatric events within the first year of treatment was only marginal higher with dolutegravir compared with raltegravir. However, monitoring of neurotoxic side-effects of dolutegravir is important. Abstract : Supplemental Digital Content is available in the text